Improved equivalent circuit and analytical model for amorphous silicon solar cells and modules - Merten, J.; Asensi, J.M.; Voz, C.; Shah, Arvind; Platz, R.; Andreu, J. (My University, 1998)
An improved equivalent circuit for hydrogenated amorphous silicon (a-Si:H) solar cells and modules is presented. It is based on the classic combination of a diode with an exponential current-voltage characteristic, of a photocurrent source plus a new term representing additional recombination losses in the i-layer of the device. This model/equivalent circuit matches the I(V) curves of a-Si:H cells over an illumination range of six orders of magnitude. The model clearly separates effects related to the technology of the device (series and parallel resistance) and effects related to the physics of the p-i-n junction (recombination losses). It also allows an effective μτ product in the i-layer of the device to be determined, characterizing its state of degradation.
Keywords: amorphous silicon solar cells and modules; analytical model; I(V) characteristics; outdoor measurements; recombination; μτ-productdegradation